"At home, no one knows": A qualitative study of retention challenges among women living with HIV in Tanzania. - Godfrey A Kisigo; James S Ngocho; Brandon A Knettel; Martha Oshosen; Blandina T Mmbaga; Melissa H Watt (PLoS ONE, 2020)
Introduction Despite the broad success of Prevention of Mother-to-Child Transmission of HIV (PMTCT) programs, HIV care engagement during the pregnancy and postpartum periods is suboptimal. This study explored the perspectives of women who experienced challenges engaging in PMTCT care, in order to better understand factors that contribute to poor retention and to identify opportunities to improve PMTCT services. Methods We conducted in-depth interviews with 12 postpartum women to discuss their experiences with PMTCT care. We used data from a larger longitudinal cohort study conducted in five PMTCT clinics in Moshi, Tanzania to identify women with indicators of poor care engagement (i.e., medication non-adherence, inconsistent clinic attendance, or high viral load). Women who met one of these criteria were contacted by telephone and invited to complete an interview. Data were analyzed using applied thematic analysis. Results We observed a common pathway that fear of stigma contributed to a lack of HIV disclosure and reduced social support for seeking HIV care. Women commonly distrusted the results of their initial HIV test and reported medication side effects after care initiation. Women also reported barriers in the health system, including difficult-to-navigate clinic transfer policies and a lack of privacy and confidentiality in service provision. When asked how care might be improved, women felt that improved counseling and follow-up, affirming patient-provider interactions, and peer treatment supporters would have a positive effect on care engagement. Conclusion In order to improve the impact of PMTCT programs, there is a need to implement active tracking and follow-up of patients, targeting individuals with evidence of poor care engagement. Tailored supportive intervention approaches may help patients to cope with both the perceived and actual impacts of HIV stigma, including navigating disclosures to loved ones and accessing social support. Fostering HIV acceptance is likely to facilitate commitment to long-term treatment.